The Place Of The Yalpizdoshe In Folk Medicine, Distributed In Fergana (Texas Journal of Agriculture and Biological Sciences, 2025)
this article highlights the morphology, chemical composition distribution and application in folk medicine of representatives of the mint family, which is distributed in the Fergana Valley.